Compaction creep of sands due to time‐dependent grain failure: Effects of chemical environment, applied stress, and grain size. Issue 10 (20th October 2014) - Brzesowsky, R. H.; Hangx, S. J. T.; Brantut, N.; Spiers, C. J.
Abstract Time‐dependent brittle creep plays a role in controlling compaction of sands and sandstones under upper crustal conditions, influencing phenomena such as production‐induced reservoir compaction, surface subsidence, and induced seismicity. Brittle creep also plays a role in determining the mechanical behavior of gouge‐rich faults. We performed uniaxial creep experiments on sand to investigate the effects of chemical environment (dry versus solution flooded), grain size (d = 196–378 µm), and applied effective stress (σa up to 30 MPa), at room temperature conditions favoring grain‐scale brittle processes. Creep measurements were complemented with acoustic emission (AE) detection and microstructural analysis to characterize the main creep mechanism. Wet samples showed much higher creep strains than dry‐tested samples. AE event counts showed a direct relation between grain failure and creep strain, with higher AE rates occurring in the wet samples. Therefore, we inferred that time‐dependent deformation was dominated by subcritical crack growth, resulting in grain failure accompanied by intergranular sliding rearrangements, and that crack growth in the presence of chemically active fluids was controlled by stress corrosion. The sensitivity of the compaction rate of the sands to d and σa can be expressed as <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3sg19t1m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ε˙∝diσaj</alternatives> where i ≈ 6 and j ≈ 21 under dry conditions and i ≈ 9 and j ≈ 15 under wet conditions. Our results were compared to a simple model based on Hertzian contact theory, linear elastic fracture mechanics, and subcritical crack growth. This model showed agreement between the observed stress and grain size sensitivities of creep, within a factor of 2.